Pediatric emergency triage systems - Hany Simon Junior; Claudio Schvartsman; Graziela de Almeida Sukys; Sylvia Costa Lima Farhat (Sociedade de Pediatria de São Paulo, 2022)
ABSTRACT Objective: The aim of this study was to perform a narrative review of the leading pediatric triage systems in emergency departments (EDs). Data source: Articles published between 1999 and 2019 were identified by searching the MEDLINE, EMBASE, and PubMed databases using the keywords "pediatric triage", "pediatric assessment tools", and "emergency department triage" with an emphasis on studies that evaluated the validation and reliability of triage systems. Data synthesis: A total of 105 articles on pediatric emergency triage systems in 12 countries were evaluated. Triage systems were divided into two groups: color-stratified triage systems and alert systems. The color-stratified triage systems included in this review were the Canadian Triage and Acuity Scale (CTAS), Manchester Triage System (MTS), Emergency Severity Index (ESI), and Australasian Triage Scale (ATS), and the alert systems included were the Paediatric Observation Priority Score (POPS), Pediatric Early Warning Score (PEWS), and Pediatric Approach Triangle (PAT). Evidence corroborates the validity and reliability of MTS, PaedCTAS, ESI version 4, PEWS, POPS, and PAT in pediatric emergency services. Conclusions: These are fundamental tools for risk classification of patients seeking treatment in EDs. Not all triage systems have been assessed for validity and reliability; nor are they well suited for all regions of the world. Employing triage systems in Brazil requires cultural adaptation and rigorous training of the local health staff, in addition to validation and reliability studies in our country, since the social and cultural context of this country differs from those where these tools were developed.